2020
DOI: 10.1016/s2542-5196(20)30197-2
|View full text |Cite
|
Sign up to set email alerts
|

Household and personal air pollution exposure measurements from 120 communities in eight countries: results from the PURE-AIR study

Abstract: Background Approximately 2•8 billion people are exposed to household air pollution from cooking with polluting fuels. Few monitoring studies have systematically measured health-damaging air pollutant (ie, fine particulate matter [PM 2•5 ] and black carbon) concentrations from a wide range of cooking fuels across diverse populations. This multinational study aimed to assess the magnitude of kitchen concentrations and personal exposures to PM 2•5 and black carbon in rural communities with a wide range of cooking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 28 publications
10
89
1
Order By: Relevance
“…There is also a lack of air pollution exposure data for important population subgroups. Men, for example, account for nearly half of the modelled disease burden attributable to household air pollution ( Institute for Health Metrics and Evaluation, 2020 ), but few studies have measured men’s exposure to PM 2.5 in a setting where solid fuel stoves were used ( Sanchez et al, 2019 , Arku et al, 2018 , Shupler et al, 2020 ). Measurements of PM 2.5 exposures in exclusive clean fuel users relative to users of solid fuel in the same setting are rare, which is important for more realistically estimating the potential air quality and health benefits of clean energy interventions ( Shupler et al, 2018 , Shupler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a lack of air pollution exposure data for important population subgroups. Men, for example, account for nearly half of the modelled disease burden attributable to household air pollution ( Institute for Health Metrics and Evaluation, 2020 ), but few studies have measured men’s exposure to PM 2.5 in a setting where solid fuel stoves were used ( Sanchez et al, 2019 , Arku et al, 2018 , Shupler et al, 2020 ). Measurements of PM 2.5 exposures in exclusive clean fuel users relative to users of solid fuel in the same setting are rare, which is important for more realistically estimating the potential air quality and health benefits of clean energy interventions ( Shupler et al, 2018 , Shupler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the annual assessment of cognition and fuel exposure every year from 2014 to 2018 is preferred, however, the CLHLS study is a nationwide cohort study, and it is difficult for investigators to survey many times. Finally, this study did not measure an individual’s actual exposure dose of HAP from biomass fuel use, the secondary polluting fuel use that also accounts for high levels of HAP [ 4 ] and the lifetime exposure to HAP. Thus, further studies should include a more objective and exhaustive assessment of individual exposure to indoor air pollution and fuel use to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biomass fuel use has been linked to household air pollution (HAP) with a higher component of particulate matter (PM) compared with the combination of biomass & liquefied petroleum gas (LPG) and LPG [ 2 ]. Studies have reported that particulate pollution from kitchens was higher when people used biomass fuels, including charcoal, wood, and grass, compared with clean fuels, including electricity and liquefied petroleum gas [ 3 , 4 ]. HAP from the burning of biomass fuels affects approximately three billion individuals worldwide [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] LPG, although a fossil fuel, does not emit black carbon, and has much lower PM 2.5 emissions than polluting fuels. 12,15,16 Using LPG for cooking can also decrease localized deforestation, and reduce time spent gathering and cooking with polluting fuels. 16,17 Historically, studies focused on determinants of clean cooking have emphasized the 'household energy ladder' model, by which improvements in socioeconomic status (SES) lead households to progressively transition to cleaner energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,16 Using LPG for cooking can also decrease localized deforestation, and reduce time spent gathering and cooking with polluting fuels. 16,17 Historically, studies focused on determinants of clean cooking have emphasized the 'household energy ladder' model, by which improvements in socioeconomic status (SES) lead households to progressively transition to cleaner energy sources. [18][19][20] However, other aspects, including consistent fuel access, safety and convenience are also important facilitators of clean cooking fuel uptake.…”
Section: Introductionmentioning
confidence: 99%